Development of Sustainable Nanogrid Road Lighting Systems - Suntiti Yoomak; Atthapol Ngaopitakkul (My University, 2020)
This paper presents the integration of a solar system into road lighting systems based on a nanogrid concept, the traditional road lighting system improvement employing light-emitting diode technologies and solar energy systems. The power quality of the proposed nanogrid road lighting system is studied and analyzed in different modes, namely, stand-alone and grid-connected, using an experimental test set. Additionally, the road lighting equipment and power quality control regulation for the grid-connected system are studied in accordance with the IEC 61000-3-2 (2018) Class C standard. The economic assessment of the proposed road lighting systems is compared with a conventional solar farm system installation in terms of discounted payback period, net present value, and internal rate of return. The results indicate that the system can effectively charge the batteries with a maximum power point based on the maximum power point tracking function and supply the road lighting system through the power from the batteries. In the grid-connected operation, the electrical energy harvested from the solar system can be sent to the electrical grid with the maximum power point. The integration of a solar system into the road lighting system based on the nanogrid concept offers remarkable economic performance in investments. Furthermore, it provides a greater economic feasibility than investing in a solar farm system, as the former is free of land costs.
Keywords: Solar Power; Advanced Battery Technologies Research